Does performance pay increase the risk of worker loneliness? - Mehrzad B. Baktash (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
Increased wages and productivity associated with performance pay can be beneficial to both employers and employees. However, performance pay can also entail unintended consequences for workers' well-being. This study is the first to systematically examine the association between performance pay and loneliness, a significant social well-being concern. Using representative survey data from Germany, I find that performance pay is positively associated with incidence, dimensions, and intensity of loneliness. Correspondingly, performance pay is negatively associated with social life satisfaction of the workers. The findings also hold in sensible instrumental variable estimations addressing the potential endogeneity of performance pay and in various robustness checks. Investigating the potential role of moderating factors reveals that the association between performance pay and loneliness is particularly large for private sector employees. Finally, implications are discussed.
Keywords: J33; I31; J32; I10; 330; Performance Pay; Loneliness; Social Life; Well-Being; SOEP